Plant extracts display synergism with different classes of antibiotics - Silva, Danielle M.; Costa, Priscilla A. da; Ribon, Andréa O. B.; Purgato, Gislaine A.; Diaz-Muñoz, Gaspar; Diaz, Marisa A.N. (Anais da Academia Brasileira de Ciências, 2019)
One manner in which plant-derived compounds exert their antibiotic potential is the synergism, a positive interaction between two compounds. Studies indicate that the use of plant extracts combined with antimicrobials may promote a significant reduction of the minimum inhibitory concentrations of antibiotics for bacterial strains. This study aimed to evaluate the activity of plant extracts and antibiotics as well as their combination on Staphylococcus aureus. The activity of 15 plant extracts was evaluated using diffusion assay. The minimum inhibitory concentrations (MICs) and the interactions between the extracts and antibiotics as well as compound emodin were evaluated with the checkerboard method. The active extracts were a hexane extract of the leaves of Baccharis dracunculifolia and the ethanol extracts of the leaves of Plectranthus ornatus, Inga edulis, Salvia officinalis and Senna macranthera. The Plectranthus ornatus extract displayed synergism with ampicillin (a β-lactam), kanamycin and gentamicin (aminoglycosides), with 8-fold reductions in the MIC. The same reduction was observed for the extracts of Salvia officinalis and Senna macranthera, which displayed the lowest MIC. Using these combinations resulted in a reduction in the minimum dose required for effective antimicrobial effects, which is interesting because it may decrease both the risk of side effects and the costs of treatment.
Keywords: Antibiotics; Bovine mastitis; Plant extract; Staphylococcus aureus